Technology At Work : At the Fire Station - Louise Spilsbury (Oxford, United Kingdom Capstone Global Library Ltd, 2008)
How does a smoke alarm work? What is Velcro made of? When are jaws of life used? Technology at Work looks at the machines and tools that make things work in our daily lives. From tiny microchips, to huge aeroplanes, this series look into the hidden world of everyday machinery and technology.
Keywords: Industry Innovation and Infrastructure; Non fiction -- Non fiction